2016
DOI: 10.1063/1.4967792
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and structural properties of ultrathin germanium nanowires by density functional theory calculations

Abstract: Employing the basin-hopping method with the Stillinger–Weber potential and penalty function, four germanium nanowires with the most stable energies were obtained at cross-section radii of 1.8 Å, 2.0 Å, 2.4 Å, and 2.9 Å, respectively. Because the coordination numbers and orbital hybridizations of Ge atoms in these nanostructures are different from bulk Ge, their density of states (DOS) profiles are distinctly different from that of bulk. Besides, the discrepancies of DOS among these nanowires arising from diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Furthermore, we compare the growth orientation of Ge NWs at temperatures below and above T e shown in Fig. 5(c), in agreement with the result of Schmidtbauer et al 10 Interestingly, at a low growth temperature, lateral NWs appear along the [1][2][3][4][5][6][7][8][9][10] direction. Scrutinizing through different positions of the NW sample grown at 220 C, we found that the NWs with 30 inclination all possess a long length, thin diameter, and small Au tips, both shown in Figs.…”
Section: (B)supporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, we compare the growth orientation of Ge NWs at temperatures below and above T e shown in Fig. 5(c), in agreement with the result of Schmidtbauer et al 10 Interestingly, at a low growth temperature, lateral NWs appear along the [1][2][3][4][5][6][7][8][9][10] direction. Scrutinizing through different positions of the NW sample grown at 220 C, we found that the NWs with 30 inclination all possess a long length, thin diameter, and small Au tips, both shown in Figs.…”
Section: (B)supporting
confidence: 88%
“…Ge nanowires (NWs) have promising electronic properties 1,2 and play an increasingly important role in various applications, such as high speed transistors, [3][4][5] photodetectors, 6,7 and the anode material of high capacity lithium-ion batteries. 8 Conventional Ge NW growth via the Au-assisted vapor-liquid-solid (VLS) process takes place above the Au-Ge eutectic temperature (T e % 361 C).…”
Section: Introductionmentioning
confidence: 99%
“…Limited work exists on the properties and exfoliation potential of individual wire chains or layers of chains within the framework of van der Waals materials. Ab initio calculations have been performed on single linear chains of individual atoms such as Fe, Ge, Au, and Te as well as different geometries of common nanowire materials SiC, GaN, BN, ZnO, ZnS, and CdS . The materials studied in this work are more complex, extending beyond monatomic or common semiconducting materials, and are known to be stable in the bulk form composed of intrinsically 1D chains.…”
mentioning
confidence: 99%